Profitability of Pakistan's Agriculture (The Pakistan Development Review, 1987)
The population of Pakistan reached the figure of 97.7 million in 1985-86. Growing at the current rate of 3.1 percent per annum, it would be over 144 million by the turn of this century. Under the pressure of such population growth, the demand for primary products would increase by a sizeable margin. An idea of this alarming situation can be formed from the projected requirements of wheat which have been estimated to be 22 million tons by the year 2000. To meet this expected demand for wheat, its production should increase by 70 percent of the existing levels, which means an annual yield growth rate of over 4.5 percent. But in the past thirty-five years i.e., during 1949-50 to 1984-85 it has grown at the rate of 2.53 percent per annum only. Supplies of other basic essentials would also be required to be increased by a similar margin to meet their increased demand. What are the sources for such large additional production? A review of past production trends shows that so far, the most important source of incremental production has been expansion in acreage. However, the available indicators suggest that the scope of additional production, through acreage increase, has since been exhausted to a great extent. The position regarding irrigation supplies, which constitute the base of additional acreage, does not appear promising any longer. Details are given in Table 1.